Variations of grain physical properties, amylose and anthocyanin of upland red rice cultivars from East Nusa Tenggara, Indonesia - Jenny E.R. Markus; Antonius S.S. Ndiwa; Shirly S. Oematan; Yosep S. Mau (Society for Indonesian Biodiversity, 2021)
Abstract. Markus JER, Ndiwa ASS, Oematan SS, Mau YS. 2021. Variations of grain physical properties, amylose and anthocyanin of upland red rice cultivars from East Nusa Tenggara, Indonesia. Biodiversitas 22: 1345-1354.  Red rice is becoming more popular nowadays due to the increasing awareness of rice consumers on its health benefits. The demands for red rice are increasing but the supply is limited, thus, local red rice cultivars can be used to fill this gap. Optimal use of local rice germplasm requires a comprehensive evaluation of their traits, and the genotypes having the most desirable traits can be selected for direct use. Several upland red rice cultivars from East Nusa Tenggara Province have been evaluated for various traits while their grain properties are still unrevealed. Information on grain properties is important, both for consumer preference and rice breeders. This study aimed to elucidate the grain physical properties, amylose, and anthocyanin of upland red rice germplasm from ENT Province, and to identify genotypes with the most desirable characters for further employment. Eighteen rice genotypes were used in this study. They were cultivated in the field, and the harvested grains were analyzed in the laboratory. Both ANOVA and descriptive statistics were used for data analysis. Substantial variations were observed on all variables, except the chalky grain percentage. The kernel length of tested genotypes was classified as long, medium, and short while the kernel shapes were slender, medium, and bold. Most tested genotypes had high head rice percentage and low to medium percentages of large and small broken kernels. Chalky grain was almost absent. Amylose content ranged from 1.0% to 28% while anthocyanin was about 1.0 - 20 mg/100 g. The evaluated genotypes were clustered into three main groups. Percentages of large and small broken kernels, and amylose content were mostly responsible for the observed variations among the rice genotypes. The red rice genotypes were diverse in the studied characters, thus, those with desirable grain characters are useful for further development and utilization.